Proses Simbolik Integrated Marketing Communication (IMC) Motif Batik Wirausaha Batik “Nimas Sekarsari” Gandusari Kabupaten Blitar - Meifilina, Andiwi; Andari, Bina (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2025)
Changes in consumer behavior require marketers to implement integrated marketing communication (IMC). The existence of the role of symbolic interaction in marketing communication is currently very important in the perception of batik consumers. The purpose of this study is to describe Symbolic Processes in Integrated Marketing Communication (IMC) of Batik Motifs Typical of Blitar Regency in Batik Entrepreneur Nimas Sekarsari Gandusari Blitar Regency. This research method is descriptive qualitative, examining the marketing communication process carried out by Batik Nimas Sekarsari Gandusari, Blitar Regency. Data collection methods include interviews, documentation, observation, and literature review. Purposive sampling is used to determine informants in interviews based on predetermined criteria. The results of this study indicate that the marketing communication in attracting consumer interest, and in order to maintain the reputation and image in the business world, include: Advertising as a way to maintain its existence in the community. Batik Nimas Sekarsari Blitar Regency also utilizes events in Blitar Regency through direct marketing activities and sales promotions to attract more consumers. Then, personal selling is carried out by Batik Nimas Sekarsari Blitar Regency through collaboration with institutions, agencies, and the government to open up opportunities to develop its business. The role of symbolic interaction in marketing communication is currently very important in consumer perception. Transaction activities between sellers and buyers are carried out on Instagram social media and also directly or face-to-face from Batik Nimas Sekarsari, Gandusari, Blitar Regency.